Peningkatan Laju Disolusi Ketoprofen yang Diformulasikan dengan Metode Self Emulsifying Drug Delivery System (SEDDS) - Nurul Muhlisah Maddeppungeng; Latifah Rahman (Jurnal Sains dan Kesehatan, 2021)
After oral administration of the drug, drug dissolution is a requirement for absorption of a drug into the systemic circulation. Based on the classification Biopharmaceutical Classification System (BCS), ketoprofen is included in class II, which has low solubility with good permeability characteristics (effective permeability in humans for ketoprofen 8.70x10-4 cm / s). Self-Emulsifying Drug Delivery System (SEDDS) can improve the bioavailability of drugs that have low solubility with high permeability. Therefore, to increase the dissolution rate, a ketoprofen formulation was carried out using the SEDDS method. Ketoprofen solubility tests were carried out on several types of oil and surfactants, namely corn oil, sunflower oil, soybean oil, oleic acid, tween 80 and span 80 using the method saturation solubility. Three formulas were made containing the active ingredient ketoprofen 50 mg, Tween 80: span 80 (3: 1) as a surfactant with a concentration of 30% (F1), 45% (F2), 60% (F3) and oil as a carrier. The dissolution test results showed that the ketoprofen formulated by the SEDDS method could increase the dissolution rate of ketoprofen, the dissolution percentage of each formula after 1 hour was 62.91% (F1), 78.09% (F2), 100.6% (F3), and 49.95% comparison. Statistical analysis using a completely randomized design showed a significant difference between dissolution rates (F1), (F2) and (F3) with comparators. The ketoprofen formula with surfactant concentration of 60% (F3) showed the highest dissolution rate compared to (F1) and (F2) as well as with comparators.